Formação docente e inclusão escolar no ensino básico de Matemática - BARROS, Aniscleide Palmeira de Sousa (Universidade Federal do Tocantins, 2023)
The purpose of this study was to investigate between the relationship between teacher training and practice and school inclusion. Aming to understand the formation of Mathematics teachers and their knowledge and didactic-pedagogical practices in the classroom as a setting for inclusion in the Basic Education, some mathematics teachers who graduated from the Licentiate Degree in Mathematics at the Federal University of Tocantins were heard, so that they could present their views on school inclusion and reports of teaching activities with the teaching of Mathematics for People with Disabilities. From the analysis of the teachers' statements, trying to understand if the initial and continuing training courses of Mathematics teachers enable the development of the education professional to deal with the cognitive and motor specificities of students with disabilities. Thus, this work has as its main objective: understand which elements (theoretical and methodological) and/or experiences the teacher uses to ensure the inclusion of students in classes and to what extent the moments of training (initial and continued) contribute to the acquisition and construction of these elements. The main theoretical reference is the work of Maria Teresa Égler Mantoan, who defends school inclusion from a perspective of the Philosophy of Difference. Regarding the methodology, we sought to analyze the responses of the interviewees, obtained through a semi-structured questionnaire, guided by a post-structuralist perspective, which considers the subject as a historical and discursive production (TADEU DA SILVA, 2005; FONSECA, 2020). From this analysis it was perceived that the teachers consider that the training courses fail to provide the construction of theoretical and methodological elements that help them in situations of teaching and learning mathematics for the students with disabilities, thus the didactic-pedagogical strategies to deal with the school inclusion are produced and applied at the moment when teachers encounter students with disabilities in their classes